Outcomes for critical illness in children with cancer: Analysis of risk factors for adverse outcome and resource utilization from a specialized center in Mexico - Cardenas-Aguirre, Adolfo; Hernandez-Garcia, Montserrat; Lira-De-Leon, Berenice; Munoz-Brugal, Yulissa L.; Wang, Huiqi; Villanueva-Diaz, Ivonne; Ruiz-Perez, Eduardo; Mijares-Tobias, Jose M.; Giles-Gonzalez, Alex O.; McArthur, Jennifer; Escamilla-Aisan, Gabriela; Arias, Anita; et al. (Frontiers in Oncology, 2022)
Children with cancer have a higher risk of adverse outcomes during critical illness than general pediatric populations. In Low- and middle-income countries, lack of resources can further negatively impact outcomes in critically ill children with cancer. In this study, we describe the outcomes of a large cohort of children with cancer including mortality and resource utilization. We performed a retrospective review of all patients admitted to our PICU between December 12th, 2013 and December 31st, 2019. Outcomes were defined as recovery or death and resource utilization was described via use of critical care interventions, Length of stay as well as PICU- and Mechanical Ventilation- free days. Overall mortality was 6.9% while mortality in the unplanned admissions was 9.1%. This remained lower than expected mortality based on PIM2 scoring. Type of PICU admission, Neurological Deterioration as a cause of PICU admission, and PIM2 were significant as risk factors in univariate analysis, but only PIM2 remained significant in the multivariate analysis. Our Study shows that high survival rates are achievable for children with cancer with critical illness in resource-limited settings with provision of high-quality critical care. Changes in organizational and clinical practice facilitating quality improvement and early identification and management of critical illness may attenuate the impact of known risk factors for mortality in this population